2016
DOI: 10.1021/acssuschemeng.6b00160
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization of Autoclaved Municipal Solid Waste Pulp and Anaerobically Treated Pulp Digestate

Abstract: In this study, the autoclaved organic fraction of municipal solid waste pulp (OFMSW) and the digestate from OFMSW pulp after anaerobic digestion (AD) were processed by hydrothermal carbonization (HTC) at 200, 250, and 300 °C for 30 min and 2 h. The focus of this work was to evaluate the potential for producing an energy-dense solid hydrochar from either OFMSW or digestate by HTC. The fate of inorganics, especially the heavy metals in hydrochar is discussed. In addition, the aqueous products were analyzed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…On the other hand, the hydrolysis of proteins in the raw SSL and the consequent formation of amides during pyrolysis and HTC are the reasons that this peak is also associated with the N-H stretching vibrations [50]. The band between 3000 cm −1 and 2800 cm −1 is ascribed to asymmetric -CHx (2925 cm −1 ) and symmetric -C-H (2850 cm −1 ) aliphatic carbons in methylene groups [51]. There are no obvious differences between the aliphatic groups present after both thermochemical processes and the originals found in the raw SSL.…”
Section: The Ph Of Biocharsmentioning
confidence: 99%
“…On the other hand, the hydrolysis of proteins in the raw SSL and the consequent formation of amides during pyrolysis and HTC are the reasons that this peak is also associated with the N-H stretching vibrations [50]. The band between 3000 cm −1 and 2800 cm −1 is ascribed to asymmetric -CHx (2925 cm −1 ) and symmetric -C-H (2850 cm −1 ) aliphatic carbons in methylene groups [51]. There are no obvious differences between the aliphatic groups present after both thermochemical processes and the originals found in the raw SSL.…”
Section: The Ph Of Biocharsmentioning
confidence: 99%
“…As far as municipal anaerobically digested sewage sludge (ADSS) is concerned, both the HTC solid and liquid by-products have been characterized, following the fate of carbon [ 23 ], nitrogen and phosphorus [ 33 , 81 , 96 ] in the product streams. The speciation of phosphorus in sludge and hydrochar has been thoroughly studied [ 76 , 94 ]. Kim et al [ 32 ] showed that HTC can be used to successfully treat ADSS, producing a carbonaceous solid product, hydrochar, with a lower moisture content and HHV than the raw digestate, making it a viable alternative to fossil solid fuels.…”
Section: Hydrothermal Carbonization Of Digestatementioning
confidence: 99%
“…Recently, digestate from organic fraction of municipal solid waste (OFMSW) was treated by HTC by Reza et al [ 94 ], obtaining an energy–dense solid hydrochar and a process water with mainly organic acids and amino acids. Zhou et al [ 97 ] underlined in their study the synergistic effect of the combination of AD and HTC, in order to evaluate a sustainable treatment for food waste in China.…”
Section: Hydrothermal Carbonization Of Digestatementioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal carbonization (HTC) is an emerging technology for producing biofuels and upgrading solid fuels [15][16][17][18]. It conveniently uses residual moisture of the feedstocks as the reaction medium due to its solvent properties at high temperatures and pressures [19].…”
Section: Introductionmentioning
confidence: 99%